Strategi Bauran Pemasaran Untuk Meningkatkan Tingkat Hunian Kamar Di Karma Kandara Resort Bali Pada Masa Pandemi Covid-19 - Ida Ayu Putu Nandana Krisyanti; Ni Luh Gde Sri Sadjuni; I Gusti Agung Gede Witarsana (Pusat Penelitian & Pengabdian kepada Masyarakat, Politeknik Pariwisata Bali, 2022)
This study aims to find out the application of a marketing mix strategy to increase room occupancy rates and to find out the strengths, weaknesses, opportunities and threats at Karma Kandara Resort Bali during the Covid-19 pandemic. During the covid-19 pandemic, there was a decrease in the number of tourists and it became a challenge for hotel management to find strategies to increase room occupancy rates. Data were collected through interview and documentation studies. The data analysis technique was carried out qualitatively, supported by a SWOT matrix analysis. The results of this study found that Karma Kandara Resort Bali already has a SWOT factor on the marketing mix variable and ST Strategy (strength-threat) by maintaining competitive prices with competitors, expanding and increasing promotional activities that have been carried out as the right SWOT strategy to increase occupancy rates. room during a pandemic